Chagas disease - Hotez, Peter (Henry Stewart Talks, 2020)
Introduction to Chagas disease, Life history stages of Trypanosoma cruzi, Epidemiology and impact, Pathogenesis, life cycle and transmission, Chronic and acute infection, Symptoms, diagnosis, treatment and prevention